IMPLEMENTASI MODEL WATERFALL DAN PENGUJIAN SYSTEM USABILITY SCALE (SUS) PADA PEMBUATAN WEBSITE PROGRAM STUDI INFORMATIKA BERBASIS WORDPRESS - Hendro Wijayanto; Yovita Kinanti Kumarahadi; Iwan Ady Prabowo (Indonesian Journal of Business Intelligence (IJUBI), 2023)
Information technology is currently developing very rapidly. Especially after the Covid-19 Pandemic which makes activities and work done online. Communication allows the exchange of information between users and recipients. The Informatics Study Program is one of the study programs at STMIK Sinar Nusantara Surakarta. Currently there are no special services available as a medium for delivering information for students and the wider community. So it is necessary to have a website that is useful for conveying information related to the activities of the Informatics Study Program. One of the widely available Content Management System is WordPress. In this study, the design and construction of a WordPress-based study program website uses the Waterfall model. Which stages in the Waterfall model consist of needs analysis, system design and software design, design and development, implementation, testing and maintenance. In the testing phase, the System Usability Scale (SUS) model is used to test the usability level or usability of the website. The test results show the usability level in the precentile ranks of 91.6%. With the category of being included in the class A scale or letter grades level and having an adjective rating level of BEST IMAGINABLE or ACCEPTABLE in the acceptability ranges. This assessment is based on 40 respondents consisting of Education Personnel, Lecturers, Students and the General Public.